The enrichment of retail e-servicescape with live-streaming integration: Insights from qualitative exploration - Xi Teng; Bamini KPD Balakrishnan (Emerald Group Publishing Limited, 2025)
Purpose – As live streaming commerce becomes increasingly growing in the e-retailing environment, it is crucial to explore its role in enriching and expanding the e-services cape model within e-retailing platforms. This paper seeks to enhance and extend the online retailing e-services cape by integrating the dimensions specific to live-streaming e-commerce. Design/methodology/approach – This research employed a qualitative approach through in-depth interviews with 15 participants, focusing on their e-retail live-streaming experiences in China. This method provided valuable insights into the perceptions and experiences of individuals engaged in live streaming as an extension of the e-services cape. Through thematic analysis, six dimensions of live streaming were identified as enrichments to the e-services cape framework. Findings – This paper proposes enriching the live-streaming dimension by introducing six sub-dimensions: attractiveness and authenticity, reliability and credibility, responsive lively interactions, social connectivity, celebrity influence and community consciousness. These sub-dimensions expand the e-services cape within online retail platforms. Research limitations/implications – It is anticipated that the findings will offer significant perspectives on how online consumers evaluate the importance of live-streaming attributes in the changing dynamics of the e-services cape. Practical implications – By exploring the importance of live-streaming and online purchasing experiences for customers, this insight can help create an online retail environment that is more engaging. Originality/value – To the best of the authors’ knowledge, this is the first study that thematically enriches the e-services cape by integrating the live-streaming dimension based on e-retailing. It provides a structured framework for future research to employ a quantitative approach to test the effectiveness of the enriched e-services cape resulting from the integration of live-streaming commerce with consumers’ behavioral responses.